2011
DOI: 10.1021/pr200003k
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and Unique Features of the Maize (Zea mays L.) Root Hair Proteome

Abstract: Root hairs are unicellular extensions of specialized epidermis cells. Under limiting conditions, they significantly increase the water and nutrient uptake capacity of plants by enlarging their root surface. Thus far, little is known about the initiation and growth of root hairs in the monocot model species maize. To gain a first insight into the protein composition of these specialized cells, the 2573 most abundant proteins of maize root hairs attached to four-day-old primary roots of the inbred line B73 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 84 publications
4
55
1
Order By: Relevance
“…Simultaneously, attempts have been made to uncover the molecular basis of RH development in the grasses at both the transcriptomic (Kwasniewski et al, 2010) and proteomic (Nestler et al, 2011;Janiak et al, 2012) levels. Mutants have provided an invaluable means for identifying the key genes that are involved in the various stages of RH formation as well as to validate conclusions that are based on large-scale analyses (Chmielewska et al, 2014).…”
Section: What Do We Know?mentioning
confidence: 99%
“…Simultaneously, attempts have been made to uncover the molecular basis of RH development in the grasses at both the transcriptomic (Kwasniewski et al, 2010) and proteomic (Nestler et al, 2011;Janiak et al, 2012) levels. Mutants have provided an invaluable means for identifying the key genes that are involved in the various stages of RH formation as well as to validate conclusions that are based on large-scale analyses (Chmielewska et al, 2014).…”
Section: What Do We Know?mentioning
confidence: 99%
“…In the studies of Brechenmacher et al (2009), Nestler et al (2011), and Janiak et al (2012, a global analysis of the root hair proteome was applied in order to identify the proteins/genes that are presumably involved in root hair formation or to characterize protein features that are conserved and typical among different plant species. The iRootHair database, with the implemented BLAST tool, can be used in analogous studies as a reference database for screening for known root hair formation-related proteins/genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that global transcriptome profiling in a wild-type/mutant system results in the rapid identification of new genes that are involved in root hair development in Arabidopsis (Jones et al, 2006) and allows the identification of new candidate genes that are presumably associated with this process in the crop plant barley (Hordeum vulgare; Kwasniewski et al, 2010). Similar approaches, applied on a proteome level, allowed the identification of new candidate proteins that can be involved in the initiation of root hair formation in barley (Janiak et al, 2012) and were used to establish a protein reference map for soybean (Glycine max) root hair cells (Brechenmacher et al, 2009) and to identify the conserved and unique protein features of root hairs in maize (Zea mays; Nestler et al, 2011). All of these studies delivered a large amount of new data that enabled the identification of known and new root hair genes and thus provided new insights into the molecular mechanisms of the complex processes of root hair formation.…”
mentioning
confidence: 99%
“…However, the findings from this model system of cell cultures might not reflect the highly specialized processes and functions of differentiated plant cells. Therefore, proteomics experiments of plant reproductive cells (pollen grains and egg cells) (18 -32), specialized leaf epidermal cells (guard cells and trichomes) (33)(34)(35)(36)(37)(38)(39)(40)(41)(42), mesophyll cells (35), and root hair cells (43)(44)(45) have been conducted (Table I). In some cases, quantitative protein expression changes in the course of cell development and in response to environmental factors have been investigated (24 -26, 29 -31, 34, 36, 37, 43).…”
mentioning
confidence: 99%
“…In this review, we focus on reviewing the current status and recent development in differentiated single-cell-type plant proteomics. We discuss technical challenges and perspectives in its integration with (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Multiple complementary gel-based and gel-free proteomic strategies have been utilized in the studies (Table I).…”
mentioning
confidence: 99%